Precipitation chemistry in semi-arid areas of Southern Africa: A case study of a rural and an industrial site - Mphepya, J. N.; Pienaar, J. J.; Galy-Lacaux, C.; Held, G.; Turner, C. R. (Springer, 2004)
Experimental data on the precipitation chemistry in the semi-arid savanna of South Africa is presented in this paper. A total of 901 rainwater samples were collected with automatic wet-only samplers at a rural site, Louis Trichardt, and at an industrial site, Amersfoort, from July 1986 to June 1999. The chemical composition of precipitation was analysed for seven inorganic and two organic ions, using ion chromatography. The most abundant ion was SO(4)(2-) and a large proportion of the precipitation is acidic, with 98% of samples at Amersfoort and 94% at Louis Trichardt having a pH below 5.6 ( average pH of 4.4 and 4.9, respectively). This acidity results from a mixture of mineral and organic acids, with mineral acids being the primary contributors to the precipitation acidity in Amersfoort, while at Louis Trichardt, organic and mineral acids contribute equal amounts of acidity. It was found that the composition of rainwater is controlled by five sources: marine, terrigenous, nitrogenous, biomass burning and anthropogenic sources. The relative contributions of these sources at the two sites were calculated. Anthropogenic sources dominate at Amersfoort and biomass burning at Louis Trichardt. Most ions exhibit a seasonal pattern at Louis Trichardt, with the highest concentrations occurring during the austral spring as a result of agricultural activities and biomass combustion, while at Amersfoort it is less pronounced due to the dominance of relatively constant industrial emissions. The results are compared to observations from other African regions.
Keywords: acid rain; chemical composition; precipitation chemistry; semi-arid savanna; wet deposition